1997
DOI: 10.1038/sj.onc.1200841
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the growth of WI-38 fibroblasts by benzyloxycarbonyl-Leu-Leu-Tyr diazomethyl ketone: evidence that cleavage of p53 by a calpain-like protease is necessary for G1 to S-phase transition

Abstract: The e ect of a calpain-selective cell permeant inhibitor, benzyloxycarbonyl Leu-Leu-Tyr diazomethylketone (ZLLY-CHN 2 ), on the serum-stimulated growth of WI-38 human ®broblasts has been investigated. Only cell permeant protease inhibitors with activity against calpains prevented progression into S-phase. Protein blotting experiments indicated that p53 immunoreactivity increased in late G 1 cells treated with ZLLY-CHN 2 . The content of p21 Waf1/Cip1 CDK inhibitor also increased, providing a mechanism for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 19 publications
2
62
1
Order By: Relevance
“…Induction of wild type p53 in MCF7 is a positive control for PS-341 activity resistant to ALLN (Figures 2a and 3c). Accumulation of wild type p53, previously shown to be sensitive to calpain as well as proteasome inhibition (Gonen et al, 1997;Kubbutat and Vousden, 1997;Pariat et al, 1997;Zhang et al, 1997), was demonstrated in MCF10 cells at the concentrations/incubation times used of the calpain inhibitors calpastatin peptide and PD150606 (Figure 4b). …”
Section: Brca1 Protein Accumulated After Alln Has An Increased Half-lifementioning
confidence: 77%
“…Induction of wild type p53 in MCF7 is a positive control for PS-341 activity resistant to ALLN (Figures 2a and 3c). Accumulation of wild type p53, previously shown to be sensitive to calpain as well as proteasome inhibition (Gonen et al, 1997;Kubbutat and Vousden, 1997;Pariat et al, 1997;Zhang et al, 1997), was demonstrated in MCF10 cells at the concentrations/incubation times used of the calpain inhibitors calpastatin peptide and PD150606 (Figure 4b). …”
Section: Brca1 Protein Accumulated After Alln Has An Increased Half-lifementioning
confidence: 77%
“…Involvement of a calpain-like activity in G 1 3 S transitions has been suggested in other systems on the basis of indirect evidence (14,15). An S-phase delay has also been observed in P. berghei parasites lacking 1 of 2 eEF1a genes, but in that case, the total cell cycle was prolonged (16).…”
Section: Discussionmentioning
confidence: 96%
“…Interference with the p53-JNK association reduced p53 ubiquitination and increased p53 half-life, suggesting that JNK might target p53 to ubiquitination and degradation (Fuchs et al, 1998). In addition to degradation by the proteasome, p53 has been shown to be cleaved by another protease, calpain, which may also serve to regulate p53 Pariat et al, 1997;Zhang et al, 1997;Atencio et al, 2000).…”
Section: Mdm2-independent Regulation Of P53 Stabilitymentioning
confidence: 99%